2014
DOI: 10.3390/rs6098923
|View full text |Cite
|
Sign up to set email alerts
|

1982–2010 Trends of Light Use Efficiency and Inherent Water Use Efficiency in African vegetation: Sensitivity to Climate and Atmospheric CO2 Concentrations

Abstract: Light and water use by vegetation at the ecosystem level, are key components for understanding the carbon and water cycles particularly in regions with high climate variability and dry climates such as Africa. The objective of this study is to examine recent trends over the last 30 years in Light Use Efficiency (LUE) and inherent Water Use 8924 Efficiency (iWUE*) for the major biomes of Africa, including their sensitivities to climate and CO2. LUE and iWUE* trends are analyzed using a combination of NOAA-AVHRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 77 publications
1
25
0
Order By: Relevance
“…Knorr et al (2010) pointed out that evaporative demand, and not just moisture availability, should be considered in phenology models. (Traore et al, 2014b) evaluated the inter-annual variability of the soil moisture of ORCHIDEE across Africa using satellite-derived estimates, and found that the new 11-layer hydrology version performed better than the 2-layer version that was used in this study. The latest version of ORCHIDEE (Naudts et al, 2015) has a more mechanistic representation of plant water stress using water potential in the soil-plant continuum, which may lead to better predictions of leaf dynamics in drought-prone regions.…”
Section: Phenology In Ecosystems Driven By Water Availabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…Knorr et al (2010) pointed out that evaporative demand, and not just moisture availability, should be considered in phenology models. (Traore et al, 2014b) evaluated the inter-annual variability of the soil moisture of ORCHIDEE across Africa using satellite-derived estimates, and found that the new 11-layer hydrology version performed better than the 2-layer version that was used in this study. The latest version of ORCHIDEE (Naudts et al, 2015) has a more mechanistic representation of plant water stress using water potential in the soil-plant continuum, which may lead to better predictions of leaf dynamics in drought-prone regions.…”
Section: Phenology In Ecosystems Driven By Water Availabilitymentioning
confidence: 93%
“…Aside from making predictions of the carbon, water and energy budgets, TBMs are routinely used in trend attribution studies. A good example in this context would be the exploration of the causes of "greening" or "browning" trends in vegetation productivity (Hickler et al, 2005;Piao et al, 2006), or the impact of such trends on resource use efficiency (Traore et al, 2014b) or the C cycle (Piao et al, 2007). The fact that the optimisation resulted in changes in the strength and location of these trends (Fig.…”
Section: Importance Of Constraining Phenology For Global Change Studiesmentioning
confidence: 99%
“…C 4 crops are generally found to have high phosphoenolpyruvate carboxylase activity (Still et al, 2003). In addition, many studies have found that C 4 plants exhibited increasing WUE in response to rising CO 2 with reductions in stomatal conductance and transpirational water loss compared to C 3 species (Manzoni et al, 2011;Traore et al, 2014). Nevertheless, WUE RS only captured the broad trend of WUE.…”
Section: Comparisons Of Wue From Flux Tower Measurements and Modis Esmentioning
confidence: 99%
“…Several studies (Boko et al, 2007;Christensen et al, 2007;Müller, Cramer, Hare, & Lotze-Campen, 2011) have shown that P in many regions in sub-Saharan Africa will change, while others (Faramarzi et al, 2013;Müller, Waha, Bondeau, & Heinke, 2014) show that dry regions will be impacted from climate change more severely than wetter areas, thus posing additional challenges to the crop security of those regions (Fisher et al, 2013;Traore et al, 2014). Overall, there is a consensus that changes in P regimes and frequency of extreme events (Haddeland et al, 2014;Llopart, Coppola, Giorgi, da Rocha, & Cuadra, 2014;Schewe et al, 2014), coupled with an increasing water usage to meet human needs, will fundamentally change water supply in many regions across the globe, with severe implications to the environment, food security, and economic prosperity in many countries (Schewe et al, 2014;Haddeland et al, 2014;Smith et al, 2014;Konar, Jason Todd, Muneepeerakul, Rinaldo, & Rodriguez-Iturbe, 2013;Morrongiello et al, 2011;Arthington, Naiman, Mcclain, & Nilsson, 2010;Vinya, Malhi, Brown, & Fisher, 2012;Vinya et al, 2013).…”
Section: Introductionmentioning
confidence: 97%